Biomechanical Evaluation of a New Fixation Method for Stabilization of Sagittal Split Ramus Osteotomy After Mandibular Advancement. (25th May 2021) - Kuik, Karel; Ho, Jean Pierre T. F.; Klop, Cornelis; de Ruiter, Maurits H. T.; Kleverlaan, Cornelis J.; de Lange, Jan; Hoekema, Aarnoud
Study Design: Biomechanical in vitro study. Mandibular advancement after sagittal split ramus osteotomy (SSRO) is a common procedure in orthognathic surgery. Several fixation methods are used for stabilization of SSRO. Objective: The aim of this study was to compare a new fixation method (gridplate) with more contemporary applied methods of fixation. Material and Methods: In this study, 50 polyurethane hemimandibles with a prefabricated SSRO were used as specimens. All hemimandibles were advanced by 8 mm and divided into 5 groups with different fixation methods: (A) one 4-hole miniplate with 4 monocortical screws; (B) two 4-hole miniplates with 8 monocortical screws; (C) one 4-hole miniplate with 4 monocortical screws and 1 bicortical screw in the retromolar area (hybrid method); (D) 3 bicortical screws in an inverted-L pattern; and (E) one 8-hole gridplate with 8 monocortical screws. Loads in newtons were recorded at displacements of the mandibular incisive edge at 1 mm, 3 mm and 5 mm. Results: Fixation with 3 bicortical screws and the gridplate presented the most stability, followed by two 4-hole miniplates. Fixation with the hybrid method or the single miniplate showed the least stability. Conclusion: According to the results of this study, the 8-hole gridplate design appears a sufficient fixation method regarding stabilization of SSRO with larger mandibular advancement.